Enhancing Physical Layer Security for Cooperative Non-Orthogonal Multiple Access Networks with Artificial Noise - Nguyen, Van-Long; Ha, Dac-Binh; Tran, Duc-Dung; Lee, Yoonill (EAI Endorsed Transactions on Industrial Networks and Intelligent Systems, 2019)
This paper does the study on the performance of the physical layer secrecy of nonorthogonal multiple access (NOMA) in downlink cooperative. The given system includes one source, multiple legitimate user pairs in the form of an eavesdropper. By applying the decode-and-forward (DF) scheme, a good user will take the information from the source to send it to the bad user in every pair, we assume that the eavesdropper will spend effort to decode the message from the bad user. To enhance the secrecy performance of given system, the artificial noise cooperative transmission scheme named ANCOTRAS is suggested. To assess the performance of the suggested scheme, we obtained the lower bound and exact closed-form expressions of secrecy outage probability by implementing statistical characteristics of signal-to-noise ratio (SNR) and signalto-interferenceplus-noise ratio (SINR). Furthermore, the secrecy performance of given system is studied basing on key parameters (including the power allocation ratio), average transmit power and amount of user pair for verifying the suggested scheme. At the end, the accuracy of final analytical outcome is reassured by using the Monte-Carlo simulation results.
Keywords: non-orthogonal multiple access; cooperative network; decode and forward; artificial noise; secrecy outage probability